P121 Prospective comparison of charcoal swabs versus near-patient direct culture plate inoculation for the culture of gonorrhoea in high-risk patients. (30th June 2016) - Harrison, Annabelle; Cheney-Lowe, Hannah; McSorley, John; Murphy, Siobhan; Brook, Gary
Abstract : Background/introduction: Gonorrhoea culture is required to monitor antibiotic resistance and is recommended for all patients known or suspected to be infected. In July 2015 our laboratory service requested us to switch from near-patient direct plating of high-risk swabs to sending charcoal swabs urgently to the lab. Aim(s)/objectives: To compare the efficacy of direct plating versus charcoal swabs for GC culture. Methods: Between July and November 2015 all patients who had a positive GC NAAT or where otherwise at high risk and had not received antibiotics had two culture swab specimens taken from the infected site: 1. a charcoal swab sent urgently to the laboratory for plating there and 2. a plastic loop specimen which was directly plated onto VCAT GC selective agar. Results: 61 patients had both specimen types taken. 41/61 (67%) directly plated specimens and 31/61 (51%) specimens transported on charcoal swabs were culture +ve (P < 0.05). For male urethral samples, plate versus charcoal, the results were 29/34 (85%) vs 22/34 (65%) (P < 0.05) and for endocervical specimens 7/14 (50%) vs 6/14 (43%) (n.s.). Numbers were too small for comparison for rectal and pharyngeal swabs. Discussion/conclusion: Despite sending the charcoal swabs urgently to the laboratory, the culture-positive rate was 24% lower than for directly plated specimens. This could not be explained through order of swabbing. Near-patient direct plating of specimens has to comply with UKAS accreditation but none the less, our results showed that this was superior to charcoal swabs transported to the lab for GC culture.